Preparation And Characterization Of Biopolymer Electrolytes Based On Pectin And Nano3 For Battery Applications - M. Vahini; M. Muthuvinayagam; M. I. N. Isa (Pleiades Publishing Ltd., 2024)
Polymer Science, Series A volume 61, pages823–831 (2019)